Endoscopic ultrasound-guided drainage of postoperative pancreatic fluid collections - Shigeru Nishiyama; Takeshi Hisa; Aki Ego; Shogo Sakata; Yui Ito; Akiharu Kudo; Takahiro Yamada; Shozo Osera; Hideki Fukushima; Shunta Ishizaki; Ryoga Hamura; Masashi Tsunematsu; et al. (International Journal of Gastrointestinal Intervention)
Background : Endoscopic ultrasound-guided drainage (EUSD) is an effective treatment for postoperative pancreatic fluid collections (POPFCs); however, standards regarding stents used for EUSD have not been established. This study analyzed the outcomes of EUSD of POPFCs at our hospital and examined the safety and effectiveness of plastic stents/tubes. Methods : This retrospective, single-center study focused on EUSD of POPFCs performed at our hospital. We examined the rates of technical success, clinical success, adverse events, and recurrence. Results : Twenty-seven patients were included in this study. The initial drainage methods comprised one nasocystic plastic tube (NPT) and one double-pigtail plastic stent (DPS) for 19 (70.4%) patients, two DPS for four (14.8%) patients, one NPT for three (11.1%) patients, and one lumen-apposing metal stent for one (3.7%) patient. The technical success and clinical success rates were both 100%. Fourteen of the 19 patients with one NPT and one DPS improved, but five patients required additional interventions and improved with fistula site dilation. Although recurrence occurred in one patient, improvement was achieved with second EUSD. Early adverse events comprised one case of bleeding for which hemostasis was achieved by performing coil embolization. Late adverse events comprised three cases of DPS migration; however, no additional intervention was required. Conclusion : The use of plastic tubes/stents is safe and effective for EUSD of POPFCs.